How to achieve low/no-fossil carbon transformations: With a special focus upon mechanisms, technologies and policies. (1st October 2017) - Zhao, Lin; Mao, Guozhu; Wang, Yutao; Du, Huibin; Zou, Hongyang; Zuo, Jian; Liu, Yong; Huisingh, Donald
Abstract: Climate change, environmental problems and consequent ecological damages due to excessive consumption of resources and to the continuing human population growth of more than 80, 000, 000 net increase per year, have damaged and continue to accelerate the devastation of numerous ecosystems. These changes have brought significant harm to humans and are imposing high costs on societal maintenance and development. In that context, low/no-fossil carbon transformations and improved material's and energy efficiency are crucial elements for reconciling human activities with sustainable societal development, which is built upon vibrant and sustainable ecosystems. The urgently needed changes are bound to be difficult to make due to the perceived contradictions between low/no-fossil-carbon systems and sustainable and economically vibrant societies. This Special Volume (SV) is comprised of thirty-three articles, which mainly focus on investigations of low/no-fossil carbon transformations in countries, regions, industries and enterprises. Some authors provided insights of ways to proceed based upon new research and development (R&D), evaluations of specific low/no-fossil carbon technologies and lessons learned from policy simulations and analyses of potential post-fossil carbon societies. This SV introductory article contains an overview of the content of the articles divided into five topics: (a) low/no-fossil carbon transformations within industrial sectors, (b) regional planning and low/no-fossil carbon developments, (c) multi-regional, low/no-fossil carbon economies, (d) specific low-fossil carbon technologies, and (e) low/no-fossil carbon policy results. Given the extensive coverage of low/no-fossil carbon transformations, the papers on mechanisms and pathways are clearly the most important contributions of this SV. The researchers focused broadly on ways to address two objectives: (a) To characterize the main factors catalyzing high-fossil carbon development and (b) To accelerate the transition to low/no fossil carbon societies. Some authors focused upon new, low/no-fossil carbon development and planning in different countries and regions, while others focused upon ways to make changes within energy-intensive industries. Additionally, some authors reported on progress in the evaluation of the effectiveness of specific low/no-fossil-carbon technologies and in the design and implementation of low/no-fossil carbon policies. The findings and recommendations of the authors are positive and encouraging. However, it is clear, that there are many additional research, policy and educational challenges, which must be solved, to establish and support systems to guide and to monitor the transformations to sustainable, equitable, livable, low/post-fossil carbon societies. Much work remains but the wisdom in the articles in this SV will help societies make the needed transitions. Highlights: The content of the articles published in this Special Volume were summarized. Problem categories about mechanism research of low/no-fossil carbon transformations were analyzed. Pathway characteristics of low/no-fossil carbon transformations at different scales were assessed. Research achievements with special, low/no-fossil carbon technologies were investigated. Promising progress in designing and implementation of low/no-fossil carbon policies were highlighted.